PRICE PERCEPTION, CHARGING INFRASTRUCTURE AND ENVIRONMENTAL CONSCIOUSNESS THAT INFLUENCE ADOPTION OF ELECTRIC VEHICLE (EV): MALAYSIA PERPSECTIVES (Journal of Technology and Operations Management, 2025)
Electric vehicles (EVs) are increasingly viewed as a sustainable solution to global issues, including climate change, carbon emissions, and energy security. This study explores key factors influencing EV adoption in Malaysia, focusing on price perception, charging infrastructure, and environmental consciousness. A quantitative method was employed, utilizing 119 completed survey responses to examine how these factors influence consumer purchase intentions. Findings indicate that price perception is not a significant barrier to EV adoption. Although high upfront costs are often viewed as a concern, government incentives, subsidies, and perceived long-term savings reduce their impact. Charging infrastructure, however, emerged as a crucial factor. Consumers highlighted the limited availability and accessibility of charging stations as a major concern, suggesting that infrastructure development is essential to support widespread adoption. This study offers valuable insights for policymakers, industry stakeholders, and environmental advocates. It emphasizes the need for continued investment in EV charging infrastructure and public awareness campaigns to promote sustainable transportation. These efforts are vital to achieving broader environmental goals and accelerating Malaysia’s transition to cleaner mobility.